Service quality and client’s satisfaction: a case study among employees at a government agency in Kota Samarahan towards counter services in Urban Transformation Centre (UTC) Kuching / Leviana Andrew, Siti Fatimah Abdul Latiff and Haniz Izyan Izzati Ali - Andrew, Leviana; Abdul Latiff, Siti Fatimah; Ali, Haniz Izyan Izzati (2021)
The study of service quality and clients’ satisfaction has been used by organisations to deliver better services to their clients. While many studies have been done on this topic from the perspective of the public towards the government service, there were few emphases from the perspective of the government servants (G2G) towards the government services offered by other government agencies. This study aimed to investigate the relationship between service quality and clients’ satisfaction among employees at a government agency towards counter services at Urban Transformation Centre (UTC) Kuching, Sarawak. The study includes all five elements of Service Quality Dimensions (SERVQUAL) which were Tangible, Reliability, Responsiveness, Assurance, and Empathy. This study includes all employees of a government agency in Kota Samarahan, Sarawak. Questionnaires were distributed to respondents through Google Form with a returned rate of 88%. It was found that empathy and responsiveness variables had a strong and positive correlation with Clients’ Satisfaction while Assurance, Reliability, and Tangibility had a moderate and positive correlation with Clients’ Satisfaction. These findings implied that clients were more satisfied with services that were handled with care and discretion as well as quickly resolving unexpected issues thus providing insights to government agencies to improve their services.